OC 8435 Multi-biomarker test strip for point-of-care screening for active tuberculosis: a five-country multi-centre test evaluation. (24th April 2019) - Corstjens, Paul; Hooij, Anouk Van; Tjon Kon Fat, Elisa; Herdigein, Shannon; Namuganga, Anna Ritah; Diergaardt, Azaria; Mutavhatsindi, Hygon; Gindeh, Awa; Mihret, Adane; Van De Spuy, Gian; Gunther, Gunar; Howe, Rawleigh; et al.
Abstract : Background: Inexpensive rapid screening tests that can be used at the point-of-care (POC) are vital to combat tuberculosis. Particularly, less invasive non-sputum-based biomarker tests for all TB forms can help controlling transmission. Availability of such tests would significantly accelerate and streamline diagnostic approaches, improve cost-efficiency and decrease unnecessary costly GeneXpert referrals. Methods: Multi-biomarker test (MBT) devices measuring levels of selections of up to six serum proteins simultaneously on a single lateral flow (LF) strip were produced. The strip contains individual capture lines for a biomarker selection allowing discrimination of TB-patients from other respiratory diseases (ORD). Only biomarkers successfully evaluated with singleplex strips (single biomarker tests) were applied to the MBT device. Quantitative signals are recorded with a low-cost handheld reader compatible with the applied luminescent up-converting particle (UCP) label. Biomarker selection and algorithms used to distinguish potential-TB and ORD are flexible. Results: Results obtained with MBT strips containing multiple test lines correlate well with singleplex LF strips. Using LF tests for 5 selected biomarkers a sensitivity of 94% and specificity of 96% could be achieved with a confirmed South African selection of 20 TB and 31 non-TB samples. Patients were designated TB positive when scoring a value above the cut-off threshold for at least 3 out of 5 biomarkers. Serum samples of potential TB patients collected at five medical research institutes (Ethiopia, Namibia, South Africa, The Gambia, Uganda) were tested locally with MBT strips comprised of CRP, SAA, IP-10, Ferritin, ApoA-I and IL-6 and results analysed to obtain an overall pan-Africa applicable signature. Conclusion: Evaluated POC applicable UCP-LF devices detecting serum biomarker signatures can help to distinguish active TB from other respiratory diseases and as such can prioritise highest-risk patients for further care. Ongoing prospective studies evaluate the MBT strip with fingerstick blood and do not require a laboratory or trained phlebotomist anymore.